Factors Influencing the Acceptance of Electronic Medical Records by Nurses: A Utaut Approach - Qonita Isnu Nabila; Rian Andriani; Wahyuddin Bagenda (LifeSciFi, 2025)
The adoption of Electronic Medical Records (EMR) has become an essential strategy for hospitals to enhance operational efficiency and improve the accuracy of medical documentation. Nevertheless, the effectiveness of EMR implementation is influenced not only by technological infrastructure but also by the level of acceptance among users, particularly nurses who interact with the system on a daily basis. This study investigates nurses’ acceptance of EMR at Purbowangi General Hospital, Kebumen, by applying the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. A quantitative survey design was employed, with data collected through questionnaires administered to all nurses actively using the EMR system. The study examined performance expectancy, effort expectancy, social influence, and facilitating conditions as independent variables, while behavioral intention and use behavior were treated as outcome variables. The data were analyzed using validity and reliability testing, followed by multiple linear regression analysis. The findings reveal that performance expectancy, effort expectancy, and social influence significantly and positively influence nurses’ intention to use EMR. In addition, behavioral intention was found to have a significant effect on actual EMR usage behavior. These results support the relevance of the UTAUT model in explaining technology acceptance in hospital environments and emphasize the need for effective training, user-friendly system design, and strong organizational support to promote sustainable EMR implementation.